The Drosophila modigliani (moi) gene encodes a HOAP-interacting protein required for telomere protection. - Raffa, G.D.; Siriaco, G.; Cugusi, S.; Ciapponi, L.; Cenci, G.; Wojcik, E.; Gatti, M. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Several proteins have been identified that protect Drosophila telomeres from fusion events. They include UbcD1, HP1, HOAP, the components of the Mre11-Rad50-Nbs (MRN) complex, the ATM kinase, and the putative transcription factor Woc. Of these proteins, only HOAP has been shown to localize specifically at telomeres. Here we show that the modigliani gene encodes a protein (Moi) that is enriched only at telomeres, colocalizes and physically interacts with HOAP, and is required to prevent telomeric fusions. Moi is encoded by the bicistronic CG31241 locus. This locus produces a single transcript that contains 2 ORFs that specify different essential functions. One of these ORFs encodes the 20-kDa Moi protein. The other encodes a 60-kDa protein homologous to RNA methyltransferases that is not required for telomere protection (Drosophila Tat-like). Moi and HOAP share several properties with the components of shelterin, the protein complex that protects human telomeres. HOAP and Moi are not evolutionarily conserved unlike the other proteins implicated in Drosophila telomere protection. Similarly, none of the shelterin subunits is conserved in Drosophila, while most human nonshelterin proteins have Drosophila homologues. This suggests that the HOAP-Moi complex, we name "terminin," plays a specific role in the DNA sequence-independent assembly of Drosophila telomeres. We speculate that this complex is functionally analogous to shelterin, which binds chromosome ends in a sequence-dependent manner.